ACTIVE MAGNETIC BEARINGS FOR FRICTIONLESS ROTATING MACHINERIES - Setiawan, Joga Dharma (ROTASI, 2006)
Active magnetic bearing (AMB) systems can support a rotor without physical contact and enable users toprecisely control rotor position and vibration as function of time or other parameters. These frictionless andprogrammable features have made AMB suitable to meeting the demand for higher speed, higher efficiency andreliability of rotating machineries in many industrial application including oil and gas production, power generationand energy conservation, clean manufacturing and transportation. This paper reviews the components and workingprinciples of AMB, which requires basic understanding of rotordynamics, electromagnetisms, power electronics andcontrol theories. Several configurations and applications of AMB are presented including design and cost issues. Thecapabilities of several major AMB world manufacturers are evaluated. The paper concludes with the summary ofinvestigation topics at several leading AMB research centers. It is hoped that this paper can provide an up-to-date,brief and yet comprehensive introduction of the AMB technology for potential users and industrial communities ingeneral.